Landings: A Settler Descendent Relationship to Land - Brett, Elizabeth (Auckland University of Technology, 2022)
Mental wellbeing is influenced by relationships with nature and land. The climate crisis is increasingly recognised as impacting mental health. In Aotearoa New Zealand, ecological loss occurs against a colonised landscape; relationship to land is entangled with historical trauma. Practicing relational psychotherapy within this context requires attention to the way that relationship to land is experienced. This heuristic self-search inquiry examines the experience of relationship to land of a settler-descended psychotherapy trainee. Drawing on Moustakas and Sela-Smith, I use a six-phase process, driven by journaling, poetry, focussing, dreams, and reflective self-inquiry and self-dialogue, to explore my experience. The resulting creative synthesis explores ambivalence and covert hostility within my experience of relationship to land. Four themes are identified: the existential distress and resentment of inevitable death; my relationship to my colonising ancestors; powerlessness, trauma, and resentment in the climate crisis; and how gender and queerness shape my relationship to land. The distress, resentment, and covert hostility to land are uncomfortable to experience; relationship to land may hold defensive aspects of avoidance, denial, and disengagement. As a self-inquiry, this research is not directly generalisable to others; however, it demonstrates the potential complexity and ambivalence of relationship to land, with implications for ecopsychology, mental health, and climate activism.
Keywords: Ecopsychology; Ecopsychotherapy; Relationship to land; Settler colonialism; Psychotherapy; Ecofeminism; Queer ecology; Ecological affect; Eco-anxiety; Climate crisis